Individual Assessment for Career Development of State Civil Apparatus - Theresia Maryati Pranatalia Pau; Dewi Syarifah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
ASN career development must be carried out based on a merit system with qualifications, competencies, performance appraisal and organizational needs in a planned and sustainable manner. Individual assessment carried out for employees to map their competencies that must be developed. It is also necessary to know the career interests of the employees by giving the RIASEC test. This study used descriptive research methods through case studies and the sample in this study was one civil servant at Government Agency X. The purpose of this research is to know the suitability between potential and work interest to occupy a position. Data collection was carried out through an individual assessment process with test and non-test methods. Data analysis of the results was carried out descriptively. The results of the individual assessment will provide an overview of the employee's potential and suitability for his career interests and able to achieve optimal performance.Pengembangan karier ASN wajib dilakukan dengan berbasis sistem merit berdasarkan kualifikasi, kompetensi, penilaian kinerja dan kebutuhan organisasi secara terencana dan berkelanjutan. Asesmen individu yang dilakukan bagi pegawai bertujuan untuk memetakan kompetensi yang harus dikembangkan. Dalam hal ini, perlu diketahui juga minat karier pegawai yang bersangkutan, salah satunya dengan memberikan tes RIASEC. Penelitian ini menggunakan metode penelitian deskriptif melalui studi kasus dan sampel dalam penelitian ini adalah satu orang PNS pada Instansi Pemerintah X. Tujuan dari penelitian ini yaitu mengetahui kesesuaian antara potensi dengan minat kerja yang dimiliki untuk menduduki suatu jabatan. Pengumpulan data dilakukan melalui proses asesmen individu dengan metode tes dan non tes. Analisis data dilakukan secara deskriptif. Hasil asesmen individu akan memberikan gambaran potensi pegawai dan kesesuaian dengan minat karier yang dimilikinya serta diharapkan pegawai mampu mencapai kinerja yang optimal.